2016
DOI: 10.4049/jimmunol.1501434
|View full text |Cite
|
Sign up to set email alerts
|

Naive Donor NK Cell Repertoires Associated with Less Leukemia Relapse after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Acute and latent human CMV cause profound changes in the NK cell repertoire, with expansion and differentiation of educated NK cells expressing self-specific inhibitory killer cell Ig-like receptors. In this study, we addressed whether such CMV-induced imprints on the donor NK cell repertoire influenced the outcome of allogeneic stem cell transplantation. Hierarchical clustering of high-resolution immunophenotyping data covering key NK cell parameters, including frequencies of CD56bright, NKG2A+, NKG2C+, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 64 publications
1
28
0
1
Order By: Relevance
“…Importantly, while NK cell alloreactivity in HLA-mismatched alloSCT can prevent GvHD, this alloreactivity is fundamental to achieving a significant antileukemic response. There are recent studies indicating an association of specific NK repertoires with less leukemia relapses after alloSCT [19,20]. Due to the very limited number of patients experiencing a relapse—One patient had a relapse within the first year after alloSCT and two additional patients relapsed after our observation period of one year—we could not establish a relationship between NKG2C expression and antileukemic response.…”
Section: Discussionmentioning
confidence: 81%
“…Importantly, while NK cell alloreactivity in HLA-mismatched alloSCT can prevent GvHD, this alloreactivity is fundamental to achieving a significant antileukemic response. There are recent studies indicating an association of specific NK repertoires with less leukemia relapses after alloSCT [19,20]. Due to the very limited number of patients experiencing a relapse—One patient had a relapse within the first year after alloSCT and two additional patients relapsed after our observation period of one year—we could not establish a relationship between NKG2C expression and antileukemic response.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, in a smaller prospective study of 106 allogeneic HSCT patients afflicted with a variety of haematological malignancies (including 37 patients with AML, 21 with MDS and 12 with CLL), Bjorklund et al . reported a protective effect of the naive NK cell repertoire (defined as NKG2C neg /NKG2A pos /CD57 neg ) on leukaemic relapse. This study directly contradicts the findings of Cichocki et al .…”
Section: And Cancer: a Double‐edged Sword?mentioning
confidence: 99%
“…Miller and colleagues recently observed increased frequency and numbers of HCMV-adaptive NK cells in patients with HCMV reactivation, with a trend toward lower leukemia early relapse rates [44]. In a separate study, Malmberg and colleagues observed lower leukemia relapse rates in patients who had higher frequencies of “naïve” (NKG2C - CD57 - NKG2A + ) NK cells following allogeneic HCT when assessed at later time points [49]. These contrasting results highlight the complexity of correlating NK cell phenotype with outcomes in the context of HCT, and may reflect differences in conditioning regimens, stem cell source, KIR-HLA mismatch, and time points chosen for NK cell assessment.…”
Section: Anti-tumor Responses Of Memory Nk Cellsmentioning
confidence: 99%